PERSEPSI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG TERHADAP PLAGIAT - 1674-1689 , Fetrio Rizal (CIVED, 2016)
ABSTRACT This study aims to reveal the perceptions of students of Building Engineering Education Department of Civil Engineering about plagiarism. This type of research is descriptive quantitative research. The population of this research is all students of Building Engineering Education Studies Program Department of Civil Engineering year in 2008-2011 as many as 94 people. The sampling technique using proportional random sampling with a sample of 49. This study has only one variable that students' perceptions about plagiarism. This research data collection tool was a questionnaire using Likert scale. The results of study indicate 75.51% students of Building Engineering Educationhas a good perception about plagiarism. That means students of Building Engineering Education understand that plagiarism is not well done. KeywordsPerception, Plagiarism.